2021
DOI: 10.3389/fncel.2021.751439
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That ITPR2-Mediated Intracellular Calcium Release in Oligodendrocytes Regulates the Development of Carbonic Anhydrase II + Type I/II Oligodendrocytes and the Sizes of Myelin Fibers

Abstract: Myelination of neuronal axons in the central nervous system (CNS) by oligodendrocytes (OLs) enables rapid saltatory conductance and axonal integrity, which are crucial for normal brain functioning. Previous studies suggested that different subtypes of oligodendrocytes in the CNS form different types of myelin determined by the diameter of axons in the unit. However, the molecular mechanisms underlying the developmental association of different types of oligodendrocytes with different fiber sizes remain elusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Zbtb20 regulates neuronal development, synaptic transmission and plasticity, memory, and emotion (Jones et al, 2018;Ripamonti et al, 2020). Itpr2 regulates somatic calcium signaling and adenosine triphosphate (ATP) release in astrocytes and astrocyte-dependent synapse elimination (Yang et al, 2016) and microglial calcium signaling and differentiation (Mei et al, 2021).…”
Section: Postnatal Age-and Brain Region-differential Transcriptomic C...mentioning
confidence: 99%
“…Zbtb20 regulates neuronal development, synaptic transmission and plasticity, memory, and emotion (Jones et al, 2018;Ripamonti et al, 2020). Itpr2 regulates somatic calcium signaling and adenosine triphosphate (ATP) release in astrocytes and astrocyte-dependent synapse elimination (Yang et al, 2016) and microglial calcium signaling and differentiation (Mei et al, 2021).…”
Section: Postnatal Age-and Brain Region-differential Transcriptomic C...mentioning
confidence: 99%
“…Mei and colleagues have revealed that Itpr2 deficiency may reduce the percentage of OLs that prefer to myelinate large‐diameter axons in the CNS. [ 33 ] In current study, we noticed that TUNEL assay did not reveal significant changes in apoptotic OLs from Itpr2 iKO mice and therefore ruled out the possible effect of Itpr2 deletion on reducing OLs numbers by cell death. However, EdU incorporation assay in OPC cultures showed an increased proportion of proliferating OPCs after Itpr2 ablation, consistent with the increased percentage of PDGFRα + or NG2 + OPCs in Itpr2 iKO mice brain.…”
Section: Discussionmentioning
confidence: 64%
“…Myelin plays a crucial role in the rapid and precise conduction of action potentials [ 1 , 2 , 3 , 4 ]. Increasing evidence has demonstrated that abnormal myelin development contributes to the disease pathogenesis including Alzheimer’s disease, major depression, and schizophrenia [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%